Individualized Phenytoin Therapy for Japanese Pediatric Patients With Epilepsy Based on CYP2C9 and CYP2C19 Genotypes. Issue 2 (April 2015) - Yamamoto, Yoshiaki; Takahashi, Yukitoshi; Imai, Katsumi; Miyakawa, Kou; Ikeda, Hiroko; Ueda, Yuki; Yamaguchi, Tokito; Nasu, Hirosato; Ohtani, Hideyuki; Shigematsu, Hideo; Kagawa, Yoshiyuki; Inoue, Yushi
Abstract : Background: The aims of this study were to identify the target dose of phenytoin (PHT) and to compare the treatment continuation rate between patients receiving conventional therapy and patients receiving individualized therapy based on genotyping of the CYP2C9 *3, CYP2C19 *2, and CYP2C19 *3 alleles. The operational definition for the target dose of PHT used in this study was the dose that yielded a steady-state PHT concentration within the range of 15–20 mcg/mL without dose-related adverse effects. Methods: We investigated 394 samples from 170 Japanese pediatric patients aged 9 months to 15 years to identify factors that influenced the target dose of PHT. We also analyzed the clinical records of 156 patients who commenced PHT therapy at our hospital and retrospectively assessed the time to treatment failure within 1 year after starting PHT therapy. During the study period, 17 patients underwent genotyping at the start of PHT therapy. If the patients had the CYP2C9 *3, CYP2C19 *2, or CYP2C19 *3 alleles, the initial dose of PHT was reduced by 10%–50% according to previous reports. The other 139 patients received conventional PHT therapy. Results: According to multiple regression analysis, the body weight, concomitant use of sulthiame, and the CYP2C9 *3, CYP2C19 *2, and CYP2C19 *3 alleles influenced the target dose of PHT. Our model explained 74% of the interindividual variability of the target dose of PHT. The total withdrawal rate in the individualized therapy group and the conventional therapy group was 23.5% and 33.1%, respectively. The adjusted hazard ratio for withdrawal of PHT therapy in the individualized therapy group was 0.37 (95% confidence interval; 0.12–1.10, P = 0.074). Conclusions: These findings suggest that genotyping can help to estimate the optimum target dose of PHT and may contribute to avoid intoxication and concentration-dependent adverse effects.